EKSISTENSI TARI BEDHAYA KETAWANG - Supriyanto, Eko (Institut Seni Indoensia Surakarta, 2018)
Bedhaya Ketawang dance is a dance developed in the Surakarta Palace. This dance in ancient times should only be performed when Jumenengan sinuwun. The development of this dance can then be danced outside the palace walls. The problem in this study is how the philosophical values contained in the Bedhaya Ketawang Dance and how the existence of the Bedhaya Ketawang Dance existed in the past with the present. The benefits of this research are entitled Philosophical Values in Bedhaya Ketawang Dance (Its existence in the past with the present) is to find philosophical values in the Bedhaya Ketawang Dance and see its existence in the past with the present. Research on Philosophical Values in Bedhaya Ketawang Dance is a type of library research. Library research is a study carried out by examining a number of libraries that are used as references. The results of this study are the philosophical values contained in the Bedhaya Ketawang Dance and the existence of the existence of the Bedhaya Ketawang Dance in the past with the present.Keywords: Bedhaya Ketawang, philosophy, existence, shift